2017
DOI: 10.4236/ijcm.2017.84027
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effectiveness of Dialectical Behavior Therapy in Clinical Symptoms, Anger Control and Emotional Regulation of Bully Children

Abstract: The present study aims to investigate the effectiveness of dialectical behavior therapy in clinical symptoms, anger control and emotional regulation of bully children. This research is a pretest-posttest quasi-experimental study design with a nonequivalent control group. The research sample comprises 24 bully children who were purposefully selected from among the students who had responded positively to the researcher's call. The participants were randomly assigned into two experimental and control groups. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We identified 11 studies examining the effectiveness of DBT in improving anger management among adolescents (see Table 1). An examination of the studies showed that these studies were carried out from 6 to 26 weeks, in correctional facilities (Shelton et al, 2011), schools (Burckhardt et al, 2018; Dadd, 2016; Ziraki & Hassan, 2017), community counseling centers (Castellanos, 2014; Denaro, 2007; Flynn et al, 2019; Geddes et al, 2013) or outpatient services of hospitals (Nelson-Gray et al, 2006; Marco et al, 2013; Woodberry & Popenoe, 2008), see Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 11 studies examining the effectiveness of DBT in improving anger management among adolescents (see Table 1). An examination of the studies showed that these studies were carried out from 6 to 26 weeks, in correctional facilities (Shelton et al, 2011), schools (Burckhardt et al, 2018; Dadd, 2016; Ziraki & Hassan, 2017), community counseling centers (Castellanos, 2014; Denaro, 2007; Flynn et al, 2019; Geddes et al, 2013) or outpatient services of hospitals (Nelson-Gray et al, 2006; Marco et al, 2013; Woodberry & Popenoe, 2008), see Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…An examination of the DBT interventions revealed that four studies used four elements of standard DBT (Flynn et al, 2019; Geddes et al, 2013; Marco et al, 2013; Woodbury & Popenoe, 2008 [skills training, individual therapy, therapist consultation, phone coaching]), one study used three elements of DBT (Dadd, 2016 [individual counseling, skills training, therapist consultation]), one study used two elements of DBT (Denaro, 2007 [skills training, individual counseling]), three studies only used DBT skills training (Burckhardt et al, 2018; Nelson-Gray et al, 2006; Ziraki & Hassan, 2017), while two studies failed to provide information regarding the DBT intervention (Castellanos, 2014; Shelton, Kesten, Zhang, & Trestman, 2011), see Table 2 for more information. Of the studies, Flynn and colleagues (2019) and Geddes and colleagues (2013) were the only studies allowing active parent participation in skills training sessions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations